Changing hearts and minds: Community conversations in Ethiopia - International Livestock Research Institute (International Livestock Research Institute, 2020)
What's the power of a community conversation? It saves lives. In Ethiopia, women and men in rural communities know little about zoonotic diseases, a major threat for both animals and humans. And deeply ingrained cultural practices dictate everything from who decides to sell animals, to who feeds them and how they are eaten. Now, community conversations are being used to empower communities to identify and analyse constraining gender relations, and to detect and treat zoonotic diseases. Read more in the ILRI 2019 Annual Report: https://www.ilri.org/news/annual-repo...